An argument for how (and why) to incentivise replication. (2018) - Howe, Piers D. L.; Perfors, Amy
Abstract: Although Zwaan et al. (2018) have made a compelling case as to why direct replications should occur more frequently than they do, they do not address how such replications attempts can best be encouraged. We propose a novel method for incentivising replication attempts and discuss some issues surrounding its implementation.